The Influence of Educational Quality, School Facilities, and Brand Image on Students' School Choice Decisions - Tambunan, Rizal L; Bukhori, Moh; Karnawati, Tin Agustina (Journal of English Language and Education, 2026)
This study examines the influence of educational quality, school facilities, and brand image on students’ decisions to enroll at RK Bintang Timur Rantauprapat Private High School. Increasing competition among private secondary schools in the Labuhanbatu region compels institutions to identify and understand the determinants shaping students’ school selection decisions. A quantitative research design with a survey method was employed. The population comprised all Grade 10 students of RK Bintang Timur Rantauprapat Private High School, totaling 146 students. A saturated sampling technique was applied, whereby the entire population served as the research sample. Data were collected through a structured questionnaire using a Likert scale. Statistical analysis was conducted using SPSS, including validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The findings reveal that educational quality, school facilities, and brand image each exert a positive and statistically significant partial effect on students’ school choice decisions. Simultaneously, the three independent variables demonstrate a significant collective influence on students’ enrollment decisions. The coefficient of determination indicates that a substantial proportion of variance in students’ decisions is explained by these variables, while the remaining variance is attributable to other factors beyond the research model. These results highlight the strategic importance of improving instructional quality, enhancing facilities, and strengthening institutional branding to attract prospective students.